The Art of Digital Transformation in Fine Arts: Liberating Contemporary Artist in Vietnam (Proceeding of the International Conference on Arts and Humanities, 2022)
The world has entered a new era with the outstanding development of information technology. All areas of human life (culture, economy, politics, education, etc.) have made significant development steps to adapt to the new context. Art is not an exception to this rule of progress. In Vietnam today, the application of information technology in the digital transformation process has brought about great changes in visual arts. This takes place from the low-level (digitizing visual elements) to the high-level (creating new art forms). Vietnamese artists are liberated from difficulties and challenges in their works such as approaching to art theory and practice of art in the digital age. The article mentions the influence of digital transformation in the artistic creation process of Vietnamese artists today. By interdisciplinary approach: fine arts, science, and technology the paper proposes a digital transformation model that has three main phases/ levels to launch digital transformation in Vietnamese visual arts. It bases on four elements: Human, Visual art, Activities, and Environment. The research paper contributes to helping artists with difficulties, challenges and to limit unnecessary risks in their professional activities: digitalizing artworks, art-forms, digitalizing the creating process as well as new way of communication, conveying artworks to their audiences, etc.
Keywords: digital transformation; arts; technology; artist liberation